Stakeholder Engagement in Ghana's Pharmaceutical Policy for Supply Chain Sustainability - Kumadey, Gifty; Agbenyegah, Albert Tchey (Acta Universitatis Danubius. Juridica, 2024)
Background: Limited empirical research exists on sustainable supply chain management in underdeveloped nations. This study focuses on pharmaceutical companies in southern Ghana, aiming to address the lack of practical information on environmentally friendly practices in meeting global pharmaceutical demand. Aim: This study examines the degree and form of stakeholder engagement in Ghana’s Pharmaceutical Policy for Supply Chain Sustainability. Setting: The study focused on top executives in Ghana s pharmaceutical industry and government institutions overseeing pharmaceutical regulations. Method: This qualitative study explores the policy framework of upstream pharmaceutical sustainable supply chain management in Ghana. Targeting top managers in the pharmaceutical industry, 18 purposively sampled interviewees provided data. Thematic analysis revealed insights through collaboration on the issue of sustainable supply chain management policy framework. Result: The study identified global bodies like World Health Organization (WHO) and the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH shaping global pharmaceutical sustainability policies. In Ghana, implemented policies encompass green procurement, healthcare waste management, and recycling. Challenges include transparency gaps, supplier engagement, regulatory complexity, limited resources, and stakeholder collaboration. Conclusion: The adoption of sustainable supply chain practices is crucial for the pharmaceutical industry in Ghana. Collaboration and inclusion of stakeholders are essential for the adoption of sustainable practices. Pharmaceutical companies in Ghana should collaborate with their suppliers, customers, regulators, and civil society organizations to promote sustainable practices throughout the supply chain. Contribution: The study suggests PMAG fosters robust collaboration and stakeholder involvement to advance sustainable supply chain practices in Ghana s upstream pharmaceutical industry.